Characterization of date palm fiber-reinforced different polypropylene matrices - Al-Otaibi, Mohammed Sh.; Alothman, Othman Y.; Alrashed, Maher M.; Anis, Arfat; Naveen, Jesuarockiam; Jawaid, Mohammad (MDPI, 2020)
In this study, the effect of different polypropylene (PP) matrices (homopolymer (HPP), impact copolymer (ICP), and recycled polypropylene (rPP)) on the mechanical, morphological, and thermal properties of date palm fiber (DPF)-reinforced PP composites was investigated. The DPFs were treated with an alkali solution, and composites were fabricated with different DPF loadings (5, 10, and 15 wt %) and lengths (less than 2 mm and 8–12 mm). It was found that the tensile properties of the DPF/ICP and DPF/rPP composites were similar to those of the DPF/HPP composites. The addition of fiber to the matrix reduced its tensile strength but increased the modulus. The alkali treatment improved the compatibility between the fibers and the matrix by removing hemicellulose and other impurities. Fourier transform infrared spectroscopy confirmed hemicellulose removal. The morphology of the alkali-treated fractured tensile specimen revealed improved adhesion and less fiber pull out. Differential scanning calorimetry revealed that the alkali treatment enhanced the crystallinity index. Thermogravimetric analysis showed that the addition of DPFs into the PP matrix reduced the thermal stability of the composite. However, the thermal stability of the treated fiber-reinforced rPP and ICP composites was similar to that of the DPF/HPP composite. Hence, rPP can be used as an alternative to HPP with DPFs.